Isolasi dan karakterisasi biokimia bakteri pembusuk buah cabai rawit - Yoga Aji Handoko; Yulius Adi Kristiawan; Yohanes Hendro Agus (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2020)
Cayenne pepper (Capsicum frutescens L.) is a species of chili that is usually consumed daily and used by the food industry. Although cayenne pepper has important roles, it is often found rotting before it is reached by consumers. Postharvest handling that did not apply good handling practices can cause decomposition of cayenne peppers. This decayed can be caused by the activity of microorganisms, such as bacteria. This study aims to isolate and examine the biochemical properties of spoilage bacteria in cayenne pepper. The stages of the experiment involved: isolation and purification of the bacteria, observation of cell morphology and colonies, and biochemical examination. The results showed that bacterial isolates in cayenne pepper had rod-shaped cell characteristics, shiny colony surfaces, and jagged colony edges. Biochemical characteristics show that these bacteria have enzyme catalase activity, phosphatase enzyme activity, are able to produce carotenoid and lecithinase. However, these bacteria can not hydrolyze starch and pectin. These biochemistry characteristics were not identic with Xanthomonas campestris. Based on the assessment of lactose fermentation, indole, methyl red, and Voges-proskauer, these bacteria could not be identified as Erwinia carotovora.